Antipsychotic Medication Review of Care Homes Residents in Neath Port Talbot (NPT) - Nermeen Ahmed (BJPsych Open)
Aims: To reduce or stop inappropriate prescriptions of antipsychotic medication in Older Adults with dementia or functional illness residing in care homes in NPT, by ensuring adequate and timely reviews of antipsychotic medications.